Utilizing GIS Application to Evaluate Pavement Condition Index: Case Study In Nasiriya City (University of Thi-Qar Journal for Engineering Sciences, 2022)
In all Countries, road pavements are recognized as one of the most critical structural components. Attention must be paid to the management of maintenance work and its timely execution in order to keep the pavement in good conditions and acceptable service level. Pavement distress check is very beneficial to the capabilities of Pavement Management Systems (PMS). The objective of this research is to connect the PAVER software database to A GIS software in order to perform spatial analysis of pavement condition and develop location-related heat distress maps based on Pavement Condition Index (PCI) values. A visual survey of the research area was conducted to evaluate the type, level, and amount of defect. The PAVER 6.5.7 software was used to calculate the PCI values for each sample unit based on the data collected from the visual survey. The data obtained by the PAVER program was integrated with ArcGIS software 10.4 in order to create heat maps utilizing spatial analysis tools . The heatmap shows the type maintenance for the study region based on PCI values, with each category of PCI values represented by different colors. Each color on this map represents a different sort of maintenance, with red indicating that the pavement requires rebuilding, yellow indicating rehabilitation, and green indicating preventative maintenance. PCI values over 85 indicate that the pavement is in excellent condition and does not need to be maintained. Using the heat map . In general, the selected roads in Nasiriya city is quite and in acceptable conditions, although there is some patching and weathering practically everywhere, and the road needs to be covered with overlay asphalt layer.